Existence and Uniqueness Results for Caputo Fractional Differential Equations with Integral Boundary Value Conditions (Journal of Partial Differential Equations, 2018)
In the paper, we consider the existence and uniqueness results for Caputofractional differential equations with integral boundary value condition. The sufficientconditions of existence and uniqueness are obtained by applying the contraction mappingprinciple, Krasnoselskii’s fixed point theorem and Leray-Schauder degree theory,which partly improves and extends the associated results of fractional differentialequations. Four examples illustrating our main results are included.